2019
DOI: 10.1002/cti2.1078
|View full text |Cite
|
Sign up to set email alerts
|

The complex existence of γδ T cells following transplantation: the good, the bad and the simply confusing

Abstract: Gamma delta (γδ) T cells are a highly heterogeneous population of lymphocytes that exhibit innate and adaptive immune properties. Despite comprising the majority of residing lymphocytes in many organs, the role of γδ T cells in transplantation outcomes is under‐researched. γδ T cells can recognise a diverse array of ligands and exert disparate effector functions. As such, they may potentially contribute to both allograft acceptance and rejection, as well as impacting on infection and post‐transplant malignancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 99 publications
0
26
0
Order By: Relevance
“…Besides, in small animal models, it was observed that gamma delta T cells could produce interleukin-17 (IL-17) to contribute acute and chronic allograft dysfunction in skin [ 38 ] and lung transplantation [ 39 ]. In contrast, some evidence showed they could produce IL-4 and IL-10 to decrease Th1 responses to achieve allograft protection [ 40 ]. For eosinophils, they are regarded as the promoting factor for inducing acute allograft rejection and the increased presence of eosinophils in peripheral blood and/or renal allograft biopsy specimen would be risky factors for outcome of acute rejection [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, in small animal models, it was observed that gamma delta T cells could produce interleukin-17 (IL-17) to contribute acute and chronic allograft dysfunction in skin [ 38 ] and lung transplantation [ 39 ]. In contrast, some evidence showed they could produce IL-4 and IL-10 to decrease Th1 responses to achieve allograft protection [ 40 ]. For eosinophils, they are regarded as the promoting factor for inducing acute allograft rejection and the increased presence of eosinophils in peripheral blood and/or renal allograft biopsy specimen would be risky factors for outcome of acute rejection [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…(I) γδ T cell subsets classified according to the usage of TCRγ-chain or δ-chain. Generally, human γδ T cells can be divided into four major groups, Vδ1, Vδ2, Vδ3 and Vδ5 γδ T cells, based on the differences of TCR δ-chain [15][16][17] (Table 1). They have different distribution and different function.…”
Section: Diversity Of Human γδ T Cell Subsetsmentioning
confidence: 99%
“…γδ T cells have been studied in the context of transplant since the 1990s, and are an important subset to consider in the field due to TCR-dependent tissue localization and a lack of MHC restriction [ 90 ]. They have been shown to quickly reconstitute along with NK cells following allogeneic hematopoietic stem cell transplant (HSCT), and are believed to effectively fill the role of αβ T cells, which take longer to recover [ 91 , 92 , 93 , 94 ].…”
Section: Reactive γδ T Cell Immunitymentioning
confidence: 99%
“…They have been shown to quickly reconstitute along with NK cells following allogeneic hematopoietic stem cell transplant (HSCT), and are believed to effectively fill the role of αβ T cells, which take longer to recover [ 91 , 92 , 93 , 94 ]. γδ T cells, in the context of transplant, have been reviewed more thoroughly elsewhere [ 73 , 90 , 95 ], revealing their multifaceted effect on overall success and survival. Following HSCT, positive correlations have been reported between elevated γδ T cell numbers and increased survival rate, while a negative correlation has been reported between γδ T cell numbers and graft-versus-host-disease (GVHD) severity.…”
Section: Reactive γδ T Cell Immunitymentioning
confidence: 99%